Interpretive Strata at Tijeras Pueblo. Issue 2 (3rd April 2022) - Thompson, Marc; Jojola, Deborah; Vredenburg, Judy
Abstract : Tijeras Pueblo Archaeological Site (LA 581) offers a variety of integrated resources encouraging appreciation of and respect for traditional Pueblo lifeways. Interpretive strata at the site are comprised of a self-guided trail, on-site museum, Tiwa World mural/map, Pueblo garden, and native plant identification. Educational outreach and programming include classroom visits, lectures, workshops, demonstrations, and a summer archaeology day camp. This paper discusses the challenges of creating text and exhibits with volunteers, and the approaches used to increase visibility at a buried site. Assessments of the relative success and shortfalls of these efforts are presented. These include detailed examinations of the elements and structure of interpretive efforts, impacts, and consequences based on descriptive and anecdotal observations.